“One of the most prolific smut writers on Tumblr” - Khaliah Reed (Persona Studies)
Most fanfiction writers never imagine the worlds they create could become television content. However, many were confronted with this possibility in the third episode of HBO’s Euphoria (2019). Kat Hernandez, a social outcast, became a well-known writer on Tumblr for her fanfiction about Harry Styles and Louis Tomlinson from One Direction. Her story, "The First Night," was brought to life through an explicit one-minute technicolour animation. This article examines the reactions to both the animation and the specific fan practice of Real Person Fanfiction (RPF) highlighted by the episode. By analysing the reactions of three groups—One Direction fans, subscribers to the "Larry Stylinson" narrative, and non-One Direction fanfiction writers—this article demonstrates how fans perform contested fan practices and (attempt to) mediate which aspects are visible to the mainstream and other fans through specific fan personas. Drawing on scholars like Christopher Moore, Mark Stewart, CarrieLynn D. Reinhard, Celia Lam and Jackie Raphael, this article investigates how idealized fan performances, often weaponized against fandom by mainstream culture, are also used internally to regulate behaviour.